2012
DOI: 10.3390/agronomy2040295
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Palmer Amaranth Management in Glufosinate-Resistant Cotton: I. Soil-Inversion, High-Residue Cover Crops and Herbicide Regimes

Abstract: A three year field experiment was conducted to evaluate the role of soil-inversion, cover crops and herbicide regimes for Palmer amaranth between-row (BR) and within-row (WR) management in glufosinate-resistant cotton. The main plots were two soil-inversion treatments: fall inversion tillage (IT) and non-inversion tillage (NIT). The subplots were three cover crop treatments: crimson clover, cereal rye and winter fallow; and sub subplots were four herbicide regimes: preemergence (PRE) alone, postemergence (POST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 52 publications
(34 reference statements)
3
27
1
Order By: Relevance
“…Similarly, Hager et al (2002) reported up to 43% reduction in soybean yield when common waterhemp interference was allowed to persist 4 wk or longer after soybean unifoliate leaf expansion. Previous research indicated several strategies for controlling GR weeds, including the use of tillage, cover crops, crop rotation, residual preemergence (PRE) herbicides, tank-mixing glyphosate with other mode-of-action herbicides, and planting cultivars or crops resistant to herbicides other than glyphosate (Aulakh et al, 2011(Aulakh et al, , 2012Aulakh, 2013;Aulakh & Jhala, 2015;Beckie, 2006;Chahal et al, 2015b;Chahal & Jhala, 2015;Norsworthy et al, 2012;Wilson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hager et al (2002) reported up to 43% reduction in soybean yield when common waterhemp interference was allowed to persist 4 wk or longer after soybean unifoliate leaf expansion. Previous research indicated several strategies for controlling GR weeds, including the use of tillage, cover crops, crop rotation, residual preemergence (PRE) herbicides, tank-mixing glyphosate with other mode-of-action herbicides, and planting cultivars or crops resistant to herbicides other than glyphosate (Aulakh et al, 2011(Aulakh et al, , 2012Aulakh, 2013;Aulakh & Jhala, 2015;Beckie, 2006;Chahal et al, 2015b;Chahal & Jhala, 2015;Norsworthy et al, 2012;Wilson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that the use of residual herbicides and herbicides with different modes of action is an important component of weed management programs (Aulakh et al 2012;Whitaker et al 2011b). …”
mentioning
confidence: 99%
“…Pendimethalin alone produced variable response with 13 and 78% control in conventional and 61 and 69% control in strip-tillage system in 2005 and 2007, respectively. Improved control in the highresidue system may be attributed to weed suppression by the cereal rye mulch (Aulakh et al 2012;Price et al 2007). Pendimethalin plus S-metolachlor controlled smooth pigweed 77% and 81% in conventional tillage system and 98% and 84% in the strip-tillage system in 2005 and 2007, respectively.…”
Section: Weed Controlmentioning
confidence: 99%